2022
DOI: 10.3389/ffgc.2022.882551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cerrado restoration on seasonal soil hydrological properties and insights on impacts of deforestation and climate change scenarios

Abstract: Knowing soil indicators during forest restoration is essentially better for understanding the recovery of ecosystem functions for water conservation. The aim of this study is to assess seasonal changes in hydrological properties of sandy soils subjected to passive restoration over 8 (F8), 11 (F11), and 46 (F46) years in the Cerrado. The soils assessed herein have the same land use history and climate conditions. Soil density (SD), moisture (SM), organic matter (SOM), resistance to penetration (SRP), infiltrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 87 publications
0
2
0
1
Order By: Relevance
“…al. (2022) andPereira et al (2022), as these authors observed an increase in soil water in ltration capacity during the wet season. Such a difference can be explained by the soil typology of the study areas in these research projects, as Histosols(Brito et al, 2022) and Entisols Quartzipsamments(Pereira et al, 2022) are soils more prone to SWR development due to their organic matter composition (da Silva et al, 2020;Lichner et al, 2018).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…al. (2022) andPereira et al (2022), as these authors observed an increase in soil water in ltration capacity during the wet season. Such a difference can be explained by the soil typology of the study areas in these research projects, as Histosols(Brito et al, 2022) and Entisols Quartzipsamments(Pereira et al, 2022) are soils more prone to SWR development due to their organic matter composition (da Silva et al, 2020;Lichner et al, 2018).…”
mentioning
confidence: 78%
“…(2022) andPereira et al (2022), as these authors observed an increase in soil water in ltration capacity during the wet season. Such a difference can be explained by the soil typology of the study areas in these research projects, as Histosols(Brito et al, 2022) and Entisols Quartzipsamments(Pereira et al, 2022) are soils more prone to SWR development due to their organic matter composition (da Silva et al, 2020;Lichner et al, 2018). The areas selected for this study encompass a clayey Latosol, a soil class with high permeability due to its microstructure, which justi es its high-water in ltration capacity throughout the year(Sano et al, 2008a).…”
mentioning
confidence: 83%
“…As alterações climáticas têm comprometido a biodiversidade do Cerrado (SALMONA et al, 2023;PEREIRA et al, 2022, OLIVEIRA et al, 2020. Avaliar a vulnerabilidade ambiental das áreas protegidas do Cerrado é fundamental para a elaboração de políticas públicas que atenuem os efeitos das mudanças climáticas no bioma (COLMAN et al, 2021).…”
Section: Introductionunclassified